Expert Histories - Cheng, Edward (Science and Technology Law Review, 2025)
Attorneys and experts often worry that being excluded in a case will have negative ramifications on an expert’s future admissibility. This symposium contribution seeks to highlight this phenomenon, as well as evaluate its normative desirability and empirical validity. Promoting the use of expert histories, for example, may create long-term incentives that help control adversarial experts. The article further develops a statistical “frailty” model to analyze a dataset of expert admissibility rulings collected and provided by Expert Profiler, LLC. The results suggest that recent exclusions may have a robust, if small, negative effect on an expert’s odds of being admitted in a future case.